2013
DOI: 10.1177/0268355513512824
|View full text |Cite|
|
Sign up to set email alerts
|

Blood pressure normalization post-jugular venous balloon angioplasty

Abstract: ObjectiveThis study is the first in a series investigating the relationship between autonomic nervous system dysfunction and chronic cerebrospinal venous insufficiency in multiple sclerosis patients. We screened patients for the combined presence of the narrowing of the internal jugular veins and symptoms of autonomic nervous system dysfunction (fatigue, cognitive dysfunction, sleeping disorders, headache, thermal intolerance, bowel/bladder dysfunction) and determined systolic and diastolic blood pressure resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…They showed that jugular vein angioplasty in patients with MS normalized the blood pressure. An increase in pressure was obtained in patients with low pressure (systolic ≤105 mmHg, diastolic ≤70 mmHg), while a decrease in this value was recorded in patients with pressure values above norm (systolic ≥130 mmHg, diastolic ≥80 mmHg) [27]. As might be expected, the beneficial hemodynamic effects of a vascular intervention should be translated into an improvement in the neurological condition of surgical patients.…”
Section: Discussionmentioning
confidence: 74%
“…They showed that jugular vein angioplasty in patients with MS normalized the blood pressure. An increase in pressure was obtained in patients with low pressure (systolic ≤105 mmHg, diastolic ≤70 mmHg), while a decrease in this value was recorded in patients with pressure values above norm (systolic ≥130 mmHg, diastolic ≥80 mmHg) [27]. As might be expected, the beneficial hemodynamic effects of a vascular intervention should be translated into an improvement in the neurological condition of surgical patients.…”
Section: Discussionmentioning
confidence: 74%
“…These results suggest that BA has the potential for improving ANS dysfunction, often observed in MS patients [17,18]. In our clinical practice, 91 % patients who seek corrective BA present with a combination of internal jugular venous (IJVs) flow obstruction ( ≥ 50 % unilateral or bilateral IJV closure) and clinical symptoms such as cognitive impairment, fatigue, sleeping disorders, headache upon waking up, and thermal intolerance [14]. Cardiovascular ANS dysfunction is known to contribute to these clinical symptoms [19][20][21][22][23], suggesting a relationship between CCSVI and ANS dysfunction.…”
Section: Neuroendocrine Responses To Transvascular Autonomic Modulatimentioning
confidence: 89%
“…Furthermore, venous BA increases both the arterial and venous blood flow [12], correcting the hypoperfusion, which is the result of venous outflow obstructions [13]. Our recent study shows that BA has also the potential of correcting BP deviation in patients presenting with CCSVI [14]. The effect of BA on BP seems to be through the resetting of high pressure baroreceptors by sensing the degree of changes in central venous pressure; the latter is mediated via changes in volume [15].…”
Section: Neuroendocrine Responses To Transvascular Autonomic Modulatimentioning
confidence: 94%
“…1,2 In a recent review article, 3 our group presented strong evidence that the route of CCSVI might stem from cardiovascular autonomic system (ANS) dysfunction in general and sympathetic dysfunction in particular. ANS dysfunction could lead to dysregulation in the arterial blood pressure 4,5 and cerebral perfusion pressure, reducing cerebral blood flow. 6,7 The dysfunction of this system can also impair cerebral autoregulation, 8 reducing transmural pressure and increasing the critical closure pressure (CrCP).…”
mentioning
confidence: 99%
“…11 The relationship between CCSVI and ANS dysfunction is further strengthened by the coexistence of CCSVI with clinical symptoms, such as cognitive impairment, fatigue, sleeping disorders, headache on awakening, and thermal intolerance. 5 Cardiovascular ANS dysfunction is known to contribute to these clinical entities. [12][13][14][15][16] Furthermore, the coexistence of CCSVI and cardiovascular ANS dysfunction has been reported in other autoimmune and neurological diseases.…”
mentioning
confidence: 99%